Effectiveness of Semantic Cloze Procedure to Improve Reading Comprehension of Weak Readers in a Primary School - Hui, Faith Chee; Chia, Noel Kok Hwee (Journal of the American Academy of Special Education Professionals, 2013)
The ability to read and write constitutes the fundamental concept of literacy and is essential to successful academic performance in school. Children who are struggling in schools are often identified as weak readers. They can be classified as either reluctant readers or disabled readers (excluding the illiterates). The former lacks the motivation to want to read while the latter is often identified as having specific reading difficulties (e.g., dyslexia and hyperlexia). Hence, such readers continue to perform poorly in class tests and school examinations. This study focused on a group of 23 Primary 4 children, who had continuously failed in their English language examinations from Primary 1 to 3 levels. A pre-/post-treatment design was used to determine whether the 23 subjects who underwent a 6-month semantic cloze procedure as a remedial teaching strategy showed significant improvement in their reading comprehension (cloze). The findings of the study suggested that whilst the subjects showed an improvement in their performance in cloze comprehension in their Semestral Examination 2 with a significant effect size as a result of the treatment, no significant inter-correlation among/between the key elements, i.e., vocabulary, word reading, reading comprehension and reading experience, was found.